Um modelo para o comportamento de manada baseado no jogo espacial dos bens públicos - Lima, Jorge Alonso (2022)
In groups and crowds, individuals can mimic the behaviour of close neighbours, ignoring rational aspects. This is herd behaviour, a crowd phenomenon largely studied in biology and economics to understand the dynamics of vulnerable systems. Bubble e ect in the stock market, animal coordination and individuals crowding together in an emergency exit to avoid danger are examples of herd behaviour situations. Understanding the reasons and the e ect of individuals choices in the crowd dynamics can reduce damages on these situations. Also, models are used to propose stock market control and better-designed emergency exits for faster responses to the crisis. This paper presents a spatial game where the level of herding is induced in the population by using a multiplayer public good game as an interaction among individuals. When individuals change from imitating the most successful strategy to copying the majority strategy in the neighbourhood, we have the herding behaviour. The objective is to understand how the return of the investment in the game and the herding induced level can a ect the total wealth, wealth distribution and level of cooperation in the population. In short, when herd behaviour had a more signi cant e ect, it was responsible for more cooperation and less wealth distribution. However, it all depended on the initial concentration of states for the simulation.